Alloy composition
Patent Information
- Application Number
- JP2024522038
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-10-14
- Filing Date
- 2022-04-21
- Publication Date
- 2025-04-30
AI Technical Summary
Existing additive manufacturing technologies, particularly metal binder jetting, face challenges in achieving high density and consistent mechanical properties in large-scale production, especially for automotive parts, due to limitations in alloy composition and processing methods.
Development of a novel alloy composition comprising iron, manganese, chromium, molybdenum, niobium, vanadium, silicon, and carbon, optimized for metal binder jetting, which forms a balanced two-phase microstructure of austenite and ferrite, enabling high sinterability and controlled mechanical properties through intercritical annealing.
The alloy composition achieves high density and improved mechanical properties, including ultimate tensile strength and ductility, comparable to conventional methods, while reducing production costs and time, making it suitable for large-scale industrial applications.
Smart Images

Figure 00000026_0000 
Figure 00000026_0001 
Figure 00000026_0002
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 255,670, filed October 14, 2021, the disclosure of which is incorporated herein by reference in its entirety.
[0002] Technical Field The present disclosure provides new alloy compositions and methods of using these compositions. [Background technology]
[0003] Like many metal processing techniques, powder metallurgy processes have evolved over the years with techniques such as warm compaction, injection molding, sinter hardening, high temperature sintering, bonding, powder forging, green machining, etc. More recently, additive manufacturing has become the latest technology gaining acceptance as the standard powder metallurgy process. There are many types of additive manufacturing processes and they can be categorized either by the nature of the feedstock utilized (powder or wire) and / or by the way the part is manufactured (laser melting or bonding with a binder in the case of powders), but one common theme is that the alloy composition (in the case of metals) and processing must be considered together to produce a high performance end product.
[0004] Like most additive manufacturing processes, metal binder jetting involves depositing powder layer by layer, with each layer and powder particles held together by a polymer adhesive. The adhesive or binder is applied to the powder bed using a printhead, much like inkjet printing. The part then needs to be sintered to its final shape and density, similar to traditional powder metallurgy processes. Compared to the competing additive manufacturing technique, laser powder bed fusion (which uses a laser to fuse powder layers together), metal binder jetting has been slower to industrialize. However, with the introduction of new and advanced machine technology, the throughput of metal binder jetting has increased significantly, and the technique is now targeted for series production of industrial parts. In addition, metal binder jetting can utilize a wider range of materials, not limited to weldable alloys. To achieve high densities (>98%), the average grain size, d 50 Fine powders with sizes in the range of 10-15 μm are used, which results in a surface quality that is approximately 20% better than laser powder bed fusion.
[0005] The automotive industry is evaluating the use of metal binder jetting to manufacture automotive parts. In particular, sheet metal applications for body and chassis components are of particular interest to automakers, as 3D printing allows for lightweight designs. Steels used in these applications are generally classified as advanced high strength steels.
[0006] Advanced high-strength or micro-alloyed steels generally utilize low alloy levels and thermo-mechanical processing (typically rolling combined with accelerated cooling) to impart superior mechanical properties. Dual-phase (DP) steels are considered a subclass of advanced high-strength steels and exhibit a microstructure consisting of hard phases (mainly martensite and / or bainite) in a matrix of ferrite. Due to their complex microstructure, duplex steels exhibit superior mechanical properties, with tensile strength generally dependent primarily on the volume fraction of martensite. Duplex steels typically contain ~20% martensite particles, which induce significant work hardening of the ferrite and therefore exhibit high ultimate tensile strength. The high percentage of ferrite phase results in high ductility with homogenous plastic flow and elimination of the Ruder's band, resulting in a more aesthetically pleasing surface without wrinkles or stretcher marks. Duplex steels also have the advantage that their lower carbon content allows them to be more weldable than steels of comparable strength, allowing them to be used in automotive exterior panels and structural reinforcements.
[0007] Producing such large products typically requires significant capital investment in stamping equipment and expensive dies. For prototyping and limited production runs, additive manufacturing can be a valuable tool to produce large numbers of designs without the need for expensive dies and equipment.
[0008] Thus, there is a need in the art for alloy compositions for use in additive manufacturing. Summary of the Invention
[0009] The present disclosure provides a composition comprising iron, about 0.01 to about 0.4% w / w manganese, about 1.3 to about 1.9% w / w chromium, up to about 0.1% w / w nickel, about 1.2 to about 1.7% w / w molybdenum, about 0.01 to about 0.4% w / w niobium, about 0.01 to about 0.4% w / w vanadium, about 1.5 to about 2% w / w silicon, and about 0.01 to about 0.20% w / w carbon.
[0010] The present disclosure also provides a method of preparing a metal powder comprising atomizing a composition described herein.
[0011] The present disclosure further provides a method of preparing a metal object comprising subjecting a metal powder described herein to metal binder jetting. [Brief description of the drawings]
[0012] This application is better understood when read in conjunction with the accompanying drawings. For the purpose of illustrating the subject matter, the drawings show exemplary embodiments of the subject matter, but the presently disclosed subject matter is not limited to the particular compositions and methods disclosed. Additionally, the drawings are not necessarily drawn to scale. [Figure 1] FIG. 1 is a dot plot of sintered density versus as-built density as a function of average particle size (d50) for 316L gas atomized stainless steel powder sintered at 1260° C. in 100% hydrogen. [Diagram 2] Figure 2 shows the phase diagram of DP600 (left) and the new alloy FSLA (right). [Diagram 3] FIG. 3 is a plot of the measured and calculated ferrite as a function of intercritical annealing temperature for FSLA alloys. [Figure 4] FIG. 4 is a CCT diagram of the FSLA alloy showing the cooling rates that transform the structure to bainite or martensite (intercritical annealing temperature 865° C., starting grain size 100 microns). [Diagram 5] Figures 5A and 5B are photographs showing the microstructure of an FSLA alloy that was intercritically annealed at 843°C and cooled at a rate of 1.3°C / s. Figure 5A is a photograph showing the typical microstructure. Figure 5B is a higher magnification photograph identifying bainite and two types of ferrite, dislocated (dark) and non-dislocated ferrite. [Figure 6] FIG. 6 is a photograph showing electron backscatter diffraction of FSLA that was intercritically annealed at 850° C. and cooled at 1.3° C. / s. [Figure 7] Figures 7A and 7B are SEM micrographs and corresponding EDS of the precipitates. Figure 7A is a micrograph / EDS of a niobium carbide particle. Figure 7B is a micrograph / EDS of a molybdenum carbide particle. [Figure 8]FIG. 8 is a bar graph showing the average precipitate diameter in microns and precipitate area fraction for two FSLA samples after intercritical annealing. [Figure 9] FIG. 9 is a line graph showing a comparison between FSLA and wrought dual phase stainless steels. [Figure 10] FIG. 10 is a bar graph showing the calculation of the intensity contribution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In this disclosure, the singular forms "a," "an," and "the" include plural references, and a reference to a particular numerical value includes at least that particular value unless the context clearly dictates otherwise. Thus, for example, a reference to "a material" is a reference to at least one of such materials and equivalents thereof known to those of skill in the art, and so forth.
[0014] When a value is expressed as an approximation by use of the descriptor "about", it will be understood that the particular value forms another embodiment. In general, the use of the term "about" indicates an approximation that may vary depending on the desired properties sought to be obtained by the disclosed subject matter and should be interpreted in the particular context in which it is used, based on its function. When present, all ranges are inclusive and combinable. That is, reference to values stated within a range includes all values within that range.
[0015] For clarity, it should be understood that certain features of the invention described herein in the context of separate embodiments may also be provided in combination in a single embodiment. That is, unless clearly incompatible or excluded, each separate embodiment is deemed combinable with any other embodiment(s), and such combinations are deemed to be separate embodiments. Conversely, various features of the invention that are described for brevity in the context of a single embodiment may also be provided separately or in any subcombination. Furthermore, it should be noted that the claims may be drafted to exclude any element. As such, this specification is intended as a predicate for the use of exclusive language such as "solely," "only," and the like, or for the use of "negative" limitations in connection with the recitation of claim elements. Finally, while an embodiment may be described as part of a series of steps or as part of a more general structure, each said step may also be considered an independent embodiment in its own right.
[0016] As described herein, the present disclosure provides metal compositions and metal powders that provide dual-phase low alloy steels. These steels are diffusion enhanced at sintering temperatures, resulting in high density. The alloying components are formulated such that upon cooling from the sintering temperature, the transformation products cause the alloy to reach the desired mechanical properties. In particular, post-sintering heat treatments (i.e., different intercritical annealing temperatures) can alter the alloy's microstructure to provide a wide range of mechanical properties. For example, the metal compositions or metal powders are useful in metal binder jetting techniques to meet a targeted set of properties with the ultimate goal of reaching the performance of competing techniques (metal stamping) for automotive applications. Thus, the metal compositions exhibit a high degree of sinterability compared to other low alloy steels used in metal binder jetting. Furthermore, once sintered, the metal compositions provide metal parts with slightly lower ductility. The use of metal binder jetting allows for the continuous production of cost-sensitive parts at much higher speeds than other additive manufacturing techniques, such as laser powder bed fusion.
[0017] metal composition The present disclosure provides compositions comprising iron and additional components including manganese, chromium, nickel, molybdenum, niobium, vanadium, silicon, and carbon. Because iron forms the basis and primary component of these compositions, they are "iron-based compositions." In some embodiments, iron is the base element. The base iron can be in the form of a powder or particles of pure iron, substantially pure iron, or iron pre-alloyed with at least one alloying element. In the iron-based powder compositions disclosed herein, the iron or pre-alloyed iron particles are combined with powders of other alloying elements to provide the final metal composition.
[0018] As used herein, "pure iron" (or "pure iron particles") refers to iron that is free of more than about 0.01% w / w of normal impurities. Elemental iron may be added to the metal composition to provide the required iron content. In some embodiments, about 2 to about 7% w / w elemental iron may be added, based on the total weight of the composition. In other embodiments, about 2, about 2.5, about 3, about 3.5, about 4, about 4.5, about 5, about 5.5, about 6, about 6.5, or about 7 elemental iron may be added, based on the total weight of the composition. In further embodiments, the solubility is from about 2 to about 6.5, from about 2 to about 6, from about 2 to about 5.5, from about 2 to about 5, from about 2 to about 4.5, from about 2 to about 4, from about 2 to about 3.5, from about 2 to about 3, from about 2 to about 2.5, from about 2.5 to about 7, from about 2.5 to about 6.5, from about 2.5 to about 6, from about 2.5 to about 5.5, from about 2.5 to about 5, from about 2.5 to about 4.5, from about 2.5 to about 4, from about 2.5 to about 3.5, from about 2.5 to about 3, from about 3 to about 7, from about 3 to about 6.5, from about 3 to about 6, from about 3 to about 5.5, from about 3 to about 5, from about 3 to about 4.5, from about 3 to about 4, from about 3 to about 3.5, from about 3.5 to about 7, from about 3.5 to about 6.5, From about 3.5 to about 6, from about 3.5 to about 5.5, from about 3.5 to about 5, from about 3.5 to about 4.5, from about 3.5 to about 4, from about 4 to about 7, from about 4 to about 6.5, from about 4 to about 6, from about 4 to about 5.5, from about 4 to about 5, from about 4 to about 4.5, from about 4.5 to about 7, from about 4.5 to about 6.5, from about 4.5 to about 6, from about 4.5 to about 5.5, from about 4.5 to about 5, from about 5 to about 7, from about 5 to about 6.5, from about 5 to about 6, from about 5 to about 5.5, from about 5.5 to about 7, from about 5.5 to about 6.5, from about 6 to about 6, from about 6 to about 6.5, or from about 6.5 to about 7 wt.% elemental iron may be added based on the total weight of the composition. In yet other embodiments, from about 3 to about 5% w / w elemental iron may be added based on the total weight of the composition.
[0019] As used herein, "substantially pure iron" (or "substantially pure iron particles") refers to iron free of about 1.0% w / w or less of typical impurities, preferably about 0.5% w / w or less, based on the total weight of the composition. Examples of substantially pure iron include highly compressible metallurgical grade iron powders. Specific examples of substantially pure iron powders include ANCORSTEEL® 1000 series pure iron powders, such as: A composition comprising iron and less than about 0.01% w / w carbon, less than about 0.14% w / w oxygen, about 0.002% w / w nitrogen, about 0.018% w / w sulfur, about 0.009% w / w phosphorus, less than about 0.01% w / w silicon, about 0.2% w / w manganese, about 0.07% w / w chromium, about 0.10% w / w copper, and about 0.08% w / w nickel (also known as ANCORSTEEL® 1000); a composition comprising iron and less than about 0.01% w / w carbon, about 0.09% w / w oxygen, about 0.001% w / w nickel, about 0.009% w / w sulfur, about 0.005% w / w phosphorus, less than about 0.01% w / w silicon, about 0.10% w / w manganese, about 0.03% w / w chromium, about 0.05% w / w copper, and about 0.05% w / w nickel (also known as ANCORSTEEL® 1000B); a composition comprising iron and less than about 0.01% w / w carbon, about 0.07% w / w oxygen, about 0.001% w / w nitrogen, about 0.007% w / w sulfur, about 0.004% w / w phosphorus, less than about 0.01% w / w silicon, about 0.07% w / w manganese, about 0.02% w / w chromium, about 0.03% w / w copper, and about 0.04% w / w nickel (also known as ANCORSTEEL® 1000C); a composition comprising iron and about 0.01% w / w carbon, about 0.02% w / w silicon, about 0.15% w / w oxygen, and about 0.015% w / w sulfur (also known as ANCORSTEEL® AMH); or A composition comprising iron, about 0.01% w / w carbon, about 0.02% w / w silicon, about 0.15% w / w oxygen, and about 0.015% w / w sulfur (also known as ANCORSTEEL® DWP200).
[0020] Other substantially pure iron powders that can be used herein include sponge iron powders, such as a composition comprising iron and about 0.02% w / w silicon dioxide, about 0.01% w / w carbon, about 0.009% w / w sulfur, and about 0.01% w / w phosphorus (also known as ANCOR MH-100 powder).
[0021] ANCORSTEEL® low alloy steel powders are substantially pure iron with low levels of alloying elements. Such low alloy steel powders include, but are not limited to: a composition comprising iron, less than about 0.01% w / w carbon, about 0.35% w / w molybdenum, about 0.15% w / w manganese, and about 0.13% w / w oxygen (also known as ANCORSTEEL® 30HP); a composition comprising iron, less than about 0.01% w / w carbon, about 0.18% w / w manganese, about 0.50% w / w molybdenum, and about 0.09% w / w oxygen (also known as ANCORSTEEL® 50HP); a composition comprising iron, less than about 0.01% w / w carbon, about 0.12% w / w manganese, about 0.86% w / w molybdenum, and about 0.08% w / w oxygen (also known as ANCORSTEEL® 85HP); A composition comprising iron, less than about 0.01% w / w carbon, about 0.12% w / w manganese, about 1.5% w / w molybdenum, and about 0.08% w / w oxygen (also known as ANCORSTEEL® 150HP).
[0022] Overall, regardless of the source of iron, the composition contains an amount of iron that is 100% w / w based on the % w / w of the other components of the composition. In other words, the amount of iron and other components of the composition add up to 100% w / w. In some embodiments, the composition contains about 85 to about 96% w / w iron. In other embodiments, the composition contains about 85, about 86, about 87, about 88, about 89, about 90, about 91, about 92, about 93, about 94, about 95, or about 96% w / w iron. In further embodiments, the composition comprises about 85 to about 96, about 85 to about 95, about 85 to about 94, about 85 to about 93, about 85 to about 92, about 85 to about 91, about 85 to about 90, about 85 to about 89, about 85 to about 88, about 85 to about 87, about 85 to about 86, about 86 to about 96, about 86 to about 95, about 86, about 94, about 86 to about 93, about 86 to about 92, about 86 to about 91, about 86 to about 90, about 86 to about 89, about 86 to about 88, about 86 to about 87, about 87 to about 96, about 87 to about 95, about 87 to about 94, about 87 to about 93, about 87 to about 92, about 87 to about 91, about 87 to about 90, about 87 to about 89, about 87 to about 88, about 88 to about 96, about 88 to about 95, about 88 to about 94, about 88 to about 93, about 88 to about 92, about 88 to about 91, about 88 to about 90, about 88 to about 89, about 89 to about 96, about 89 to about 95, about 89 to about 94m about 8 9 to about 93, about 89 to about 92, about 89 to about 91, about 89 to about 90, about 90 to about 96, about 90 to about 95, about 90 to about 94, about 90 to about 93, about 90 to about 92, The composition comprises about 90 to about 91, about 91 to about 96, about 91 to about 95, about 91 to about 94, about 91 to about 93, about 91 to about 92, about 92 to about 96, about 92 to about 95, about 92 to about 94, about 92 to about 93, about 93 to about 96, about 93 to about 95, about 93 to about 94, about 94 to about 96, about 94 to about 95, or about 95 to about 96% w / w iron. In further embodiments, the composition comprises about 94 to about 96% w / w iron. In yet other embodiments, the composition comprises about 94.1 to about 95.4% w / w iron. In further embodiments, the composition comprises about 94.11 to about 95.44% w / w iron.
[0023] As previously mentioned, the composition includes additional components. These components are balanced in the composition to provide a dual-phase microstructure. In some embodiments, the elements that form austenite in the alloy (e.g., carbon, copper, nickel) are balanced with elements that form ferrite (e.g., chromium, molybdenum, silicon, etc.) to form a dual-phase microstructure. In addition to helping form the desired microstructure, the additional elements contribute to the transformation products (e.g., bainite and martensite) that form when the alloy is cooled. These transformation products result in increased work hardening rates and sintered metal products with high strength (e.g., high ultimate tensile strength) and high ductility.
[0024] In some embodiments, the composition comprises about 0.01 to about 0.4% w / w manganese. In certain aspects, the composition comprises about 0.01, about 0.01, about 0.02, about 0.03, about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, about 0.09, about 0.1, about 0.11, about 0.12, about 0.13, about 0.14, about 0.15, about 0.16, about 0.17, about 0.18, about 0.19, about 0. In another embodiment, the composition comprises about 0.1 to about 0.35, about 0.1 to about 0.3, about 0.1 to about 0.25, about 0.1 to about 0.2, about 0.1 to about 0.15, about 0.25 to about 0.4, about 0.25 to about 0.35, about 0.25 to about 0.3, or about 0.3 to about 0.4% w / w manganese. In further embodiments, the composition comprises about 0.1 to about 0.3% w / w manganese. In other embodiments, the composition comprises about 0.15 to about 0.25% w / w manganese. In further embodiments, the composition comprises about 0.2% w / w manganese.
[0025] In other embodiments, the composition comprises about 1.3 to about 1.9% chromium w / w. In certain aspects, the composition comprises about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, or about 1.9% chromium w / w. In other embodiments, the composition comprises about 1.3 to about 1.8, about 1.3 to about 1.7, about 1.3 to about 1.6, about 1.3 to about 1.5, about 1.3 to about 1.4, about 1.4 to about 1.9, about 1.4 to about 1.8, about 1.4 to about 1.7, about 1.4 to about 1.6, about 1.4 to about 1.5, about 1.5 to about 1.9, about 1.5 to about 1.8, about 1.5 to about 1.7, about 1.5 to about 1.6, about 1.6 to about 1.9, about 1.6 to about 1.8, about 1.6 to about 1.7, about 1.7 to about 1.9, about 1.7 to about 1.8, or about 1.8 to about 1.9% w / w chromium. In other embodiments, the composition comprises about 1.4 to about 1.8% w / w chromium. In further embodiments, the composition comprises about 1.5 to about 1.7% w / w chromium. In yet other embodiments, the composition comprises about 1.55 to about 1.65% w / w chromium. In yet other embodiments, the composition comprises about 1.6% w / w chromium.
[0026] In a further embodiment, the composition is devoid of nickel, i.e. contains 0% w / w nickel, making the composition less of a health and safety concern.
[0027] Alternatively, the composition may include nickel. In yet other embodiments, the composition includes about 0.1% w / w or less of nickel. Thus, in certain aspects, the composition includes about 0.09, about 0.08, about 0.07, about 0.06, about 0.05, about 0.04, about 0.03, about 0.02, or about 0.01% w / w or less of nickel.
[0028] In further embodiments, the composition comprises about 0.04 to about 0.1% nickel. In certain aspects, the composition comprises about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, about 0.09, or about 0.1% w / w nickel. In other aspects, the composition comprises about 0.04 to about 0.1, about 0.04 to about 0.09, about 0.04 to about 0.08, about 0.04 to about 0.07, about 0.04 to about 0.06, about 0.04 to about 0.05, about 0.05 to about 0.1, about 0.05 to about 0.09, about 0.05 to about 0.08, about 0.05 to about 0.07, about 0.05 to about 0.08 ... The composition comprises about 0.06, about 0.06 to about 0.1, about 0.06 to about 0.09, about 0.06 to about 0.08, about 0.06 to about 0.07, about 0.07 to about 0.1, about 0.07 to about 0.09, about 0.07 to about 0.08, about 0.08 to about 0.1, about 0.08 to about 0.09, or about 0.09 to about 0.1% w / w nickel. In further embodiments, the composition comprises about 0.05 to about 0.07% w / w nickel. In yet other embodiments, the composition comprises about 0.05% w / w nickel. In yet other embodiments, the composition comprises about 0.1% w / w nickel.
[0029] The composition also includes molybdenum. Among other reasons, the molybdenum-rich carbides formed provide additional strengthening while limiting grain growth during heat treatment. In other embodiments, the composition includes about 1.2 to about 1.7% w / w molybdenum. In certain aspects, the composition includes about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, or about 1.7% w / w molybdenum. In other embodiments, the composition comprises about 1.2 to about 1.7, about 1.2 to about 1.6, about 1.2 to about 1.5, about 1.2 to about 1.4, about 1.2 to about 1.3, about 1.3 to about 1.7, about 1.3 to about 1.6, about 1.3 to about 1.5, about 1.3 to about 1.4, about 1.4 to about 1.7, about 1.4 to about 1.6, about 1.4 to about 1.5, about 1.5 to about 1.7, about 1.5 to about 1.6, or about 1.6 to about 1.7% w / w molybdenum. In further embodiments, the composition comprises about 1.3 to about 1.6% w / w molybdenum. In yet other embodiments, the composition comprises about 1.4 to about 1.5% w / w molybdenum. In further embodiments, the composition comprises about 1.45% w / w molybdenum. In other embodiments, the composition comprises about 1.5% w / w molybdenum.
[0030] The composition further comprises niobium. In particular, niobium provides a dual phase of austenite and ferrite, thereby allowing higher carbon levels to be utilized. Additionally, the niobium-rich carbides formed provide additional strength while inhibiting grain growth during heat treatment. In some embodiments, the composition comprises about 0.01 to about 0.4% w / w niobium. In certain aspects, the composition comprises about 0.01, about 0.02, about 0.03, about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, about 0.09, about 0.1, about 0.11, about 0.12, about 0.13, about 0.14, about 0.15, about 0.16, about 0.17, about 0.18, about 0.19, about 0.20 , about 0.21, about 0.22, about 0.23, about 0.24, about 0.25, about 0.26, about 0.27, about 0.28, about 0.29, about 0.30, about 0.31, about 0.32, about 0.33, about 0.34, about 0.35, about 0.36, about 0.37, about 0.38, about 0.39, or about 0.4% w / w niobium. In other embodiments, the composition comprises from about 0.1 to about 0.35, about 0.1 to about 0.3, about 0.1 to about 0.25, about 0.1 to about 0.2, about 0.1 to about 0.15, about 0.25 to about 0.4, about 0.25 to about 0.35, about 0.25 to about 0.3, or about 0.3 to about 0.4% w / w niobium. In further embodiments, the composition comprises about 0.1 to about 0.3% w / w niobium. In other embodiments, the composition comprises about 0.15 to about 0.2% w / w niobium. In further embodiments, the composition comprises about 0.18% w / w niobium.
[0031] The composition also includes vanadium. In particular, vanadium, alone or in combination with niobium, provides a dual phase of austenite and ferrite, thereby allowing higher carbon levels to be utilized. Additionally, the vanadium-rich carbides formed provide additional strength. In some embodiments, the composition includes about 0.01 to about 0.4% w / w vanadium. In particular aspects, the composition includes about 0.01, about 0.02, about 0.03, about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, about 0.09, about 0.1, about 0.11, about 0.12, about 0.13, about 0.14, about 0.15, about 0.16, about 0.17, about 0.18, about 0.19, about 0.20, about 0.21, about 0.22, about 0.23, about 0.24, about 0.25, about 0.26, about 0.27, about 0.28, about 0.29, about 100, about 110, about 120, about 130, about 140, about 150, about 160, about 170, about 180, about 190, about 200, about 210, about 220, about 230, about 240, about 250, about 260, about 270, about 280, about 290, about 300, about 310, about 320, about 330, about 340, about 350, about 360, about 370, about 380, about 390, about 400, about 410, about 420, about 430, about 440, about In another embodiment, the composition comprises about 0.1 to about 0.35, about 0.1 to about 0.3, about 0.1 to about 0.25, about 0.1 to about 0.2, about 0.1 to about 0.15, about 0.25 to about 0.4, about 0.25 to about 0.35, about 0.25 to about 0.3, or about 0.3 to about 0.4% w / w vanadium. In further embodiments, the composition comprises about 0.1 to about 0.3% w / w vanadium. In other embodiments, the composition comprises about 0.15 to about 0.2% w / w vanadium. In further embodiments, the composition comprises about 0.18% w / w vanadium.
[0032] The composition further comprises silicon. In some embodiments, the composition comprises about 1.5 to about 2% w / w silicon. In certain embodiments, the composition comprises about 1.5 to about 2, about 1.5 to about 1.9, about 1.5 to about 1.8, about 1.5 to about 1.7, about 1.5 to about 1.6, about 1.6 to about 2, about 1.6 to about 1.9, about 1.6 to about 1.8, about 1.6 to about 1.7, about 1.7 to about 2, about 1.7 to about 1.9, about 1.7 to about 1.8, about 1.8 to about 2, about 1.8 to about 1.9, or about 1.9 to about 2% w / w silicon. In other embodiments, the composition comprises about 1.5 to about 1.8% w / w silicon. In further embodiments, the composition comprises about 1.5 to about 1.7% w / w silicon. In yet another embodiment, the composition comprises about 1.6 to about 1.7% w / w silicon. In a further embodiment, the composition comprises about 1.6% w / w silicon.
[0033] The compositions of the present disclosure also include carbon. With a lower amount of carbon, the metal composition is more suitable for welding. In some embodiments, the composition includes about 0.01 to about 0.20% w / w carbon. In certain aspects, the composition includes about 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, about 0.12, about 0.13, about 0.14, about 0.15, about 0.16, about 0.17, about 0.18, about 0.19, or about 0.2% w / w carbon. In other aspects, the composition includes about 0.05 to about 0.14% w / w carbon. In further aspects, the composition includes about 0.1 to about 0.14% w / w carbon. In yet other aspects, the composition includes about 0.14% w / w carbon. In yet another embodiment, the composition comprises less than about 0.16 w / w carbon.
[0034] The compositions of the present disclosure optionally include additional components such as sulfur, oxygen, nitrogen, or combinations thereof. Such components are typically present in the iron powder incorporated into the compositions of the present disclosure. In one example, the composition includes sulfur. In some embodiments, the composition includes about 0.001 to about 0.015% w / w sulfur. In certain aspects, the composition includes about 0.001, about 0.002, about 0.003, about 0.004, about 0.005, about 0.006, about 0.007, about 0.008, about 0.009, about 0.01, about 0.011, about 0.012, about 0.013, about 0.014, or about 0.015% w / w sulfur.In other embodiments, the composition comprises about 0.001 to about 0.015, about 0.001 to about 0.014, about 0.001 to about 0.013, about 0.001 to about 0.012, about 0.001 to about 0.011, about 0.001 to about 0.01, about 0.001 to about 0.009, about 0.001 to about 0.008, about 0.001 to about 0.007, about 0.001 to about 0.006, about 0.001 to about 0.005, about 0.001 to about 0.004, about 0.001 to about 0.003, about 0.001 to about 0.002, about 0.0025 to about 0.015, about 0.0025 to about 0.014, about 0.0025 to about 0.013, about 0.0025 to about 0.012, about 0.0025 to about 0.011, about 0.0025 to about 0.01, about 0.0025 to about 0.009, about 0.0025 to about 0.008, about 0.0025 to about 0.007, about 0.0025 to about 0.006, about 0.0025 to about 0.005, about 0.0025 to about 0.004, about 0.0 0.025 to about 0.003, about 0.005 to about 0.015, about 0.005 to about 0.014, about 0.005 to about 0.013, about 0.005 to about 0.012, about 0.005 to about 0.011, about 0.005 to about 0.01, about 0.005 to about 0.009, about 0.005 to about 0.008, about 0.005 to about 0.007, about 0.005 to about 0.006, about 0.0075 to about 0.005, about 0.0075 to about 0.004, about 0.0075 to about 0.015, about The composition comprises about 0.0075 to about 0.014, about 0.0075 to about 0.013, about 0.0075 to about 0.012, about 0.0075 to about 0.011, about 0.0075 to about 0.01, about 0.01 to about 0.015, about 0.01 to about 0.014, about 0.01 to about 0.013, about 0.01 to about 0.012, about 0.01 to about 0.011, about 0.0125 to about 0.015, about 0.0125 to about 0.014, or about 0.0125 to about 0.013% w / w sulfur. In further embodiments, the composition comprises about 0.005 to about 0.01% w / w sulfur. In yet other embodiments, the composition comprises about 0.006 to about 0.008% w / w sulfur. In yet another embodiment, the composition comprises about 0.007% w / w sulfur.
[0035] In another example, the composition of the present disclosure comprises oxygen. In some embodiments, the composition comprises about 0.01 to about 0.1% w / w oxygen. In certain aspects, the composition comprises about 0.01, about 0.02, about 0.03, about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, about 0.09, or about 0.1% w / w oxygen. In other aspects, the composition comprises about 0.01 to about 0.09, about 0.01 to about 0.08, about 0.01 to about 0.07, about 0.01 to about 0.06, about 0.01 to about 0.05, about 0.01 to about 0.04, about 0.01 to about 0.03, about 0.01 to about 0.02, about 0.02 to about 0.1, about 0.02 to about 0.09, about 0. 0.02 to about 0.08, about 0.02 to about 0.07, about 0.02 to about 0.06, about 0.02 to about 0.05, about 0.02 to about 0.04, about 0.02 to about 0.03, about 0.03 to about 0.1, about 0.03 to about 0.09, about 0.03 to about 0.08, about 0.03 to about 0.07, about 0.03 to about 0.06, about 0.03 to about 0. 05, about 0.03 to about 0.04, about 0.04 to about 0.1, about 0.04 to about 0.09, about 0.04 to about 0.08, about 0.04 to about 0.07, about 0.04 to about 0.06, about 0.04 to about 0.05, about 0.05 to about 0.1, about 0.05 to about 0.09, about 0.05 to about 0.08, about 0.05 to about 0.07, about 0.0 The composition comprises about 0.5 to about 0.06, about 0.06 to about 0.1, about 0.06 to about 0.09, about 0.06 to about 0.08, about 0.06 to about 0.07, about 0.07 to about 0.1, about 0.07 to about 0.09, about 0.07 to about 0.08, about 0.08 to about 0.1, about 0.08 to about 0.09, or about 0.09 to about 0.1% w / w oxygen. In a further embodiment, the composition comprises about 0.04 to about 0.08% w / w oxygen. In yet another embodiment, the composition comprises about 0.05 to about 0.07% w / w oxygen. In yet another embodiment, the composition comprises about 0.06% w / w sulfur.
[0036] In further examples, the composition comprises about 0.01 to about 0.02% nitrogen. In certain embodiments, the composition comprises about 0.011, about 0.012, about 0.013, about 0.014, about 0.015, about 0.016, about 0.017, about 0.018, about 0.019, or about 0.2% w / w nitrogen. In some embodiments, the composition comprises from about 0.011 to about 0.019, from about 0.011 to about 0.018, from about 0.011 to about 0.017, from about 0.011 to about 0.016, from about 0.011 to about 0.015, from about 0.011 to about 0.014, from about 0.011 to about 0.013, from about 0.011 to about 0.012, from about 0.012 to about 0.02, from about 0.012 to about 0.019, or from about 0. 0.012 to about 0.018, about 0.012 to about 0.017, about 0.012 to about 0.016, about 0.012 to about 0.015, about 0.012 to about 0.014, about 0.012 to about 0.013, about 0.013 to about 0.02, about 0.013 to about 0.019, about 0.013 to about 0.018, about 0.013 to about 0.017, about 0.013 to about 0.016, about 0.013 to about 0 .015, about 0.013 to about 0.014, about 0.014 to about 0.02, about 0.014 to about 0.019, about 0.014 to about 0.018, about 0.014 to about 0.017, about 0.014 to about 0.016, about 0.014 to about 0.015, about 0.015 to about 0.02, about 0.015 to about 0.019, about 0.015 to about 0.018, about 0.015 to about 0.017, about The composition comprises about 0.015 to about 0.016, about 0.016 to about 0.2, about 0.016 to about 0.019, about 0.016 to about 0.018, about 0.016 to about 0.017, about 0.017 to about 0.02, about 0.017 to about 0.019, about 0.017 to about 0.018, about 0.018 to about 0.02, about 0.018 to about 0.019, or about 0.019 to about 0.02% w / w nitrogen. In further embodiments, the composition comprises about 0.005 to about 0.015% w / w nitrogen. In other embodiments, the composition comprises about 0.01% w / w nitrogen.
[0037] Method for preparing metal powder The metal compositions described herein can be utilized to prepare metal powders for use in the processes described below. In some embodiments, the metal powders are prepared by atomizing the metal compositions described herein. For example, the metal compositions are gas atomized or water atomized to provide the metal powder. In certain aspects, the metal compositions are gas atomized. In other aspects, the metal compositions are water atomized.
[0038] The metal powders of the present disclosure are fine powders, i.e., have a small average particle size. This results in high density and high surface quality of the metal objects. In some embodiments, the surface quality of the metal objects is about 20% better than similar objects prepared using laser powder bed fusion. The low average particle size of the metal powders allows for a high surface quality of the metal objects. 10 , d 50 , and / or d 90 It can be measured by the value.
[0039] The metal powder has a diameter of about 1 to about 10 μm. 10 In some embodiments, the composition can have a particle size of about 1, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, or about 10 μm. 10 In another embodiment, the metal powder has a particle size of about 1 to about 10 μm, about 1 to about 9, about 1 to about 8, about 1 to about 7, about 1 to about 6, about 1 to about 5, about 1 to about 4, about 1 to about 3, about 1 to about 2, about 2 to about 10, about 2 to about 9, about 2 to about 8, about 2 to about 7, about 2 to about 6, about 2 to about 5, about 2 to about 4, about 2 to about 3, about 3 to about 10, about 3 to about 9, about 3 to about 8, about 3 to about 7, about 3 to about 6, d of about 3 to about 5, about 3 to about 4, about 4 to about 10, about 4 to about 9, about 4 to about 8, about 4 to about 7, about 4 to about 6, about 4 to about 5, about 5 to about 10, about 5 to about 9, about 5 to about 8, about 5 to about 7, about 5 to about 6, about 6 to about 10, about 6 to about 9, about 6 to about 8, about 6 to about 7, about 7 to about 10, about 7 to about 9, about 7 to about 8, about 8 to about 10, about 8 to about 9, or about 9 to about 10 μm 10 It has a particle size.
[0040] Metal powders can alternatively be 10 In addition to the particle size, d of about 10 to about 20 μ 50In certain embodiments, the metal powder has a particle size of about 10, about 11, about 12, about 13, about 14, about 15, about 16, about 17, about 18, about 19, or about 20 μm. 50 In other embodiments, the composition has a particle size of about 10 to about 19, about 10 to about 18, about 10 to about 17, about 10 to about 16, about 10 to about 15, about 10 to about 14, about 10 to about 13, about 10 to about 12, about 10 to about 11, about 11 to about 20, about 11 to about 19, about 11 to about 18, about 11 to about 17, about 11 to about 16, about 11 to about 15, about 11 to about 14, about 11 to about 13, about 11 to about 12, about 12 to about 20, about 12 to about 19, about 12 to about 18, about 12 to about 17, about 12 to about 16, about 12 to about 15, about 12 to about 14, about 12 to about 13, about 13 about 13 to about 19, about 13 to about 18, about 13 to about 17, about 13 to about 16, about 13 to about 15, about 13 to about 14, about 14 to about 20, about 14 to about 19, about 14 to about 18, about 14 to about 17, about 14 to about 16, about 14 to about 15, about 15 to about 20, about 15 to about 19, about 15 to about 18, about 15 to about 17, about 15 to about 16, about 16 to about 20, about 16 to about 19, about 16 to about 18, about 16 to about 17, about 17 to about 20, about 17 to about 19, about 17 to about 18, about 18 to about 20, about 18 to about 19, or about 19 to about 20 μm 50 It has a particle size.
[0041] Metal powder is d 10 and / or d 50 Instead of or in addition to the particle size of about 20 to about 30 μm 90 In certain embodiments, the metal powder has a particle size of about 20, about 21, about 22, about 23, about 24, about 25, about 26, about 27, about 28, about 29, or about 30 μm. 50In another embodiment, the composition has a particle size of about 20 to about 29, about 20 to about 28, about 20 to about 27, about 20 to about 26, about 20 to about 25, about 20 to about 24, about 20 to about 23, about 20 to about 22, about 20 to about 21, about 21 to about 30, about 21 to about 29, about 21 to about 28, about 21 to about 27, about 21 to about 26, about 21 to about 25, about 21 to about 24, about 21 to about 23, about 21 to about 22, about 22 to about 30, about 22 to about 29, about 22 to about 28, about 22 to about 27, about 22 to about 26, about 22 to about 25, about 22 to about 24, about 22 to about 23, about 23 25 to about 30, about 23 to about 29, about 23 to about 28, about 23 to about 27, about 23 to about 26, about 23 to about 25, about 23 to about 24, about 24 to about 30, about 24 to about 29, about 24 to about 28, about 24 to about 27, about 24 to about 26, about 24 to about 25, about 25 to about 30, about 25 to about 29, about 25 to about 28, about 25 to about 27, about 25 to about 26, about 26 to about 30, about 26 to about 29, about 26 to about 28, about 26 to about 27, about 27 to about 30, about 27 to about 29, about 27 to about 28, about 28 to about 30, about 28 to about 29, or about 29 to about 30 μm 50 It has a particle size.
[0042] The compositions described herein may also be combined with excipients useful for preparing metal objects (e.g., green processing, sintering, and / or annealing). In some embodiments, the excipient is a lubricant or binder. The lubricants and binders that can be used as described herein are those commonly employed by the powder metallurgy industry. See, for example, the lubricants described in US-4,834,800; US-4,483,905; US-5,298,055; US-5,368,630; US-5,498,276; US-5,330,792; US-6,602,315; US-5,290,336, the disclosures of which are incorporated herein by reference in their entirety. In other embodiments, the excipient is graphite, a stearate (such as zinc stearate, lithium stearate, manganese stearate, calcium stearate, etc.), zinc phosphate, boric acid, acetic acid, phosphoric acid, citric acid, an amide lubricant (such as ethylene bisstearamide), polysilazane, polyurea silazane, polythiourea silazane, polycarbosilane, polysilane, polysiloxane, polyborosilazane, polyaminosilazane, polyaminoborane, polyalazanes, polyborazanes, polyphosphazenes, polyphosphinoboranes, polyglycols (such as polyethylene glycol or polypropylene glycol), glycerin, polyvinyl alcohol, a homopolymer or copolymer of vinyl acetate, polymers, cellulose ester or ether resins, methacrylic acid polymers or copolymers, alkyl resins, polyurethane resins, polyester resins, dibasic organic acids (such as azelaic acid), polyethers (liquid or solid), acrylic resins, cellulose ester resins, hydroxyalkyl cellulose resins, thermoplastic phenolic resins, polyvinylpyrrolidone, polyethylene oxide, low melting solid polymers or waxes including paraffin wax (e.g., polymers or waxes having a softening temperature of less than 200°C such as polyester, polyethylene, epoxy, urethane, paraffin, ethylene bisstearamide, or cottonseed wax), polyolefins, including hydrogenated derivatives, C 14-24Alkyl triglycerides and their derivatives, hydrogenated vegetable oils (such as cottonseed oil, soybean oil, jojoba oil, or mixtures thereof), polyvinyl acetate, polyethylene, cellulose ester, or polyvinylpyrrolidone. In certain embodiments, the excipient is polyethylene, ethylene bisstearamide, paraffin wax, or polyvinyl acetate, or a combination thereof.
[0043] Within the scope of the present disclosure, the components of the metallurgical powder compositions may be added, combined, and / or bound together in any order.
[0044] Methods of using metal compositions / powders The compositions and powders described herein are useful in a variety of applications. In some embodiments, the present disclosure provides methods for preparing metal objects using these compositions and powders. The desired shape and type of metal object can be determined by one of ordinary skill in the art. In certain embodiments, the metal object is a billet, bar, rod, wire, strip, plate, or sheet. In some embodiments, the metal object is an automobile part. In other embodiments, the metal object is a sheet material for an automobile part. In further embodiments, the metal object is a sheet material for the body of an automobile part. In yet other embodiments, the metal object is a sheet material for an automobile chassis part.
[0045] The method includes subjecting a metal composition or powder to metal binder jetting. A person skilled in the art will understand the steps involved in metal binder jetting.
[0046] In summary, metal binder jetting involves depositing a composition or powder onto a substrate in layers. The substrate does not form part of the desired metal object product, but instead is a medium designed to support the final metal object. One skilled in the art will be able to determine the type of substrate and number of layers desired to produce the desired metal object. In some embodiments, the layers of the metal composition or powder are two or more layers.
[0047] Each layer of metal composition or powder is held or bonded using a liquid binder. In some embodiments, the liquid binder is a polymer. In other embodiments, the liquid binder is a polymeric adhesive. A person skilled in the art will be able to select an appropriate polymeric adhesive depending on the metal object to be prepared. In some aspects, the polymeric adhesive is polyethylene, ethylene bisstearamide, or other wax, among others. The liquid binder can be applied to each layer of metal powder using a print head. A person skilled in the art will be able to select an appropriate print head depending on factors such as the desired metal object, metal composition, or powder, among others. The liquid binder is applied at a thickness required by the desired metal object. In some embodiments, the binder is applied at a thickness of about 1 to about 100 microns. In further embodiments, the binder is applied at a thickness of about 1, about 5, about 10, about 20, about 30, about 40, about 50, about 60, about 70, about 80, about 90, or about 100 microns. In still other embodiments, the conjugate is from about 1 to about 90, from about 1 to about 80, from about 1 to about 70, from about 1 to about 60, from about 1 to about 50, from about 1 to about 40, from about 1 to about 30, from about 1 to about 20, from about 1 to about 10, from about 10 to about 100, from about 10 to about 90, from about 10 to about 80, from about 10 to about 70, from about 10 to about 60, from about 10 to about 50, from about 10 to about 40, from about 10 to about 30, from about 10 to about 20, from about 20 to about 100, from about 20 to about 90, from about 20 to about 80, from about 20 to about 70, from about 20 to about 60, from about 20 to about 50, from about 20 to about 40, from about 20 to about 30, from about 40 to about 100, from about 30 to about In a further embodiment, the binder is applied to a thickness of about 50 microns. In a further embodiment, the binder is applied to a thickness of about 50 microns.
[0048] Once the metal object is prepared using metal binder jetting, the metal object is sintered. Doing so results in a desired shape and / or density of the metal object. One of ordinary skill in the art would be able to determine appropriate sintering conditions, including, among others, temperature. In some embodiments, the metal object is sintered at a temperature that provides the metal object's crystal structure that is body-centered cubic (BCC) ferrite. In other embodiments, the metal object is sintered at a temperature that provides the metal object's crystal structure that is face-centered cubic austenite (FCC). In further embodiments, the metal object is sintered at a temperature that provides the metal object's crystal structure that is BCC and FCC. In yet other embodiments, the sintered metal object has a ratio of BCC to face-centered cubic austenite (FCC) of about 1:1. In further embodiments, the metal object comprises about 10 to about 50% w / w BCC based on the weight of the metal object. In certain embodiments, the metal object comprises about 10, about 20, about 30, about 40, or about 50% w / w BCC based on the weight of the metal object. In further aspects, the metal object comprises about 10 to about 40, about 10 to about 30, about 10 to about 20, about 20 to about 50, about 20 to about 40, about 20 to about 30, about 30 to about 50, about 30 to about 40, or about 40 to about 50% w / w BCC based on the weight of the metal object. In other embodiments, the metal object comprises about 10% to about 50% w / w FCC based on the weight of the metal object. In certain embodiments, the metal object comprises about 10, about 20, about 30, about 40, or about 50% w / w VCC based on the weight of the metal object. In further aspects, the metal object comprises about 10 to about 40, about 10 to about 30, about 10 to about 20, about 20 to about 50, about 20 to about 40, about 20 to about 30, about 30 to about 50, about 30 to about 40, or about 40 to about 50% w / w FCC based on the weight of the metal object. In further embodiments, the sintering temperature is about 700 to about 1500° C. In other embodiments, the sintering temperature is about 700, about 750, about 800, about 850, about 900, about 950, about 1000, about 1050, about 1100, about 1150, about 1200, about 1250, about 1300, about 1350, about 1400, about 1450, or about 1500° C.In further embodiments, the sintering temperature is about 700 to about 1400, about 700 to about 1300, about 700 to about 1200, about 700 to about 1100, about 700 to about 1000, about 700 to about 900, about 700 to about 800, about 800 to about 1500, about 800 to about 1400, about 800 to about 1300, about 800 to about 1200, about 800 to about 1100, about 800 to about 1000, about 800 to about 900, about 900 to about 1500, about 900 to about 1400, about 900 to about 1300, about 900 to about 1400, about 900 to about 1500, about 900 to about 1400, about 900 to about 1300, about 900 to about 1500, about 900 to about 1500, about 900 to about 1400, about 900 to about 1300, about 900 to about 1600, about 900 to about 1700, about 900 to about 1800, about 900 to about 1900, about 1900 to about 2000, about 1900 to about 2100, about 1900 to about 2200, about 1900 to about 2300, about 1900 to about 2400, about 1900 to about 2500, about 1900 to about 2600, about 1900 to about 2700, about 1900 to about 2800, 00 to about 1200, about 900 to about 1100, about 900 to about 1000, about 1000 to about 1500, about 1000 to about 1400, about 1000 to about 1300, about 1000 to about 1200, about 1000 to about 1100, about 1100 to about 1500, about 1100 to about 1400, about 1100 to about 1300, about 1100 to about 1200, about 1200 to about 1400, about 1200 to about 1300, about 1300 to about 1500, about 1300 to about 1400, or about 1400 to about 1500 ° C. In yet another embodiment, the sintering temperature is about 1200 to about 1380 ° C.
[0049] After sintering, the sintered metal body has a high density. In some embodiments, the density of the sintered metal body is at least about 7.2 g / cm 3 In other embodiments, the density of the sintered metal body is about 7.2 to about 7.8. In further embodiments, the density of the sintered metal body is about 7.2, about 7.3, about 7.4, about 7.5, about 7.6, about 7.7, or about 7.8 g / cm. 3 In yet other embodiments, the density of the sintered metal body is about 7.2 to about 7.7, about 7.2 to about 7.6, about 7.2 to about 7.5, about 7.2 to about 7.4, about 7.2 to about 7.3, about 7.3 to about 7.8, about 7.3 to about 7.7, about 7.3 to about 7.6, about 7.3 to about 7.5, about 7.3 to about 7.4, about 7.4 to about 7.8, about 7.4 to about 7.7, about 7.4 to about 7.6, about 7.4 to about 7.5, about 7.5 to about 7.8, about 7.5 to about 7.7, about 7.5 to about 7.6, about 7.6 to about 7.8, about 7.6 to about 7.7, or about 7.7 to about 7.8 g / cm. 3 It is.
[0050] The sintered metal body may then be subjected to additional steps including, but not limited to, annealing. One advantage of the metal compositions or powders of the present disclosure is that metal bodies having two phases can be produced. Thus, the metal body can be intercritically annealed at temperatures that change the levels of austenite and ferrite. Thus, heat treatments can be developed that produce different properties in the same alloy. For example, if a material with higher strength is desired, an intercritical annealing temperature can be designed where a higher austenite level exists, and then a cooling rate can be utilized to produce a higher level of martensite / bainite, resulting in higher strength. In another example, if a more ductile material is desired, an intercritical annealing temperature can be utilized to produce a higher level of ferrite, thereby resulting in a metal body with lower strength but higher elongation. As a further example, if a steel material with optimal strength and ductility is desired, the cooling rate is adjusted. In doing so, the cooling rate allows for the formation of the appropriate microstructure. An advantage of the present disclosure is that metal powders for metal binder jetting can be tailored to meet a variety of properties.
[0051] To provide desirable mechanical properties, the metal bodies prepared herein have optimized ultimate tensile strength, ductility, or a combination thereof. This can be achieved by adjusting the amount of bainite, the amount of martensite, or a combination thereof. In certain embodiments, the amount of bainite in the metal body is about 20 to about 30% w / w based on the weight of the metal body. In other embodiments, the amount of bainite in the metal body is about 20, about 21, about 22, about 23, about 24, about 25, about 26, about 27, about 28, about 29, about, or about 30% w / w based on the weight of the metal body. In further embodiments, the amount of bainite, martensite, or a combination thereof in the metal object is about 20 to about 29, about 20 to about 28, about 20 to about 27, about 20 to about 26, about 20 to about 25, about 20 to about 24, about 20 to about 23, about 20 to about 22, about 20 to about 21, about 21 to about 30, about 21 to about 29, about 21 to about 28, about 21 to about 27, about 21 to about 26, about 21 to about 25, about 21 to about 24, about 21 to about 23, about 21 to about 22, about 22 to about 30, about 22 to about 29, about 22 to about 28, about 22 to about 27, about 22 to about 26, about 22 to about 25, about 22 to about 24, about 22 to about 23, about 23 to about 30, about 23 to about 29, about 23 to about 28, about 23 to about 27, about 23 to about 26, about 23 to about 25, about 23 to about 24, about 24 to about 30, about 24 to about 29, about 24 to about 28, about 24 to about 27, about 24 to about 26, about 24 to about 25, about 25 about 25 to about 29, about 25 to about 28, about 25 to about 27, about 25 to about 26, about 26 to about 30, about 26 to about 29, about 26 to about 28, about 26 to about 27, about 27 to about 30, about 27 to about 29, about 27 to about 28, about 28 to about 30, about 28 to about 29, or about 29 to about 30% w / w.
[0052] One of ordinary skill in the art would be able to determine appropriate annealing conditions, including, inter alia, temperature. In further embodiments, the intercritical annealing temperature is about 600 to about 1000°C. In other embodiments, the intercritical annealing temperature is about 600°C, about 650°C, about 700°C, about 750°C, about 800°C, about 850°C, about 900°C, about 950°C, or about 1000°C. In further embodiments, the intercritical annealing temperature is about 600 to about 1000°C, about 600 to about 900°C, about 600 to about 800°C, about 600 to about 700°C, about 650 to about 1000°C, about 650 to about 900°C, about 650 to about 800°C, about 650 to about 700°C, about 700 to about 1000°C, about 700 to about 900°C, about 700 to about 800°C, about 750 to about 1000°C, about 750 to about 900°C, about 750 to about 800°C, about 800 to about 1000°C, about 800 to about 900°C, about 850 to about 1000°C, about 850 to about 900°C, about 900 to about 1000°C, or about 950 to about 1000°C.
[0053] Aspects Aspect 1. A composition comprising iron, and about 0.01 to about 0.4% w / w manganese, about 1.3 to about 1.9% w / w of chromium; Nickel, not exceeding about 0.1% w / w; about 1.2 to about 1.7% w / w of molybdenum, about 0.01 to about 0.4% w / w of niobium, about 0.01 to about 0.4% w / w vanadium, about 1.5 to about 2% w / w silicon, and about 0.01 to about 0.20% w / w of carbon; A composition comprising:
[0054] Embodiment 2. The composition of claim 1, comprising 0% w / w nickel.
[0055] Aspect 3. The composition of claim 1, comprising about 0.04 to about 0.1%, preferably about 0.05 to about 0.07%, or preferably about 0.05% w / w, or preferably about 0.1% w / w of nickel.
[0056] Aspect 4. A composition according to any one of the preceding claims, comprising about 0.1 to about 0.3%, preferably about 0.15 to about 0.25%, or preferably about 0.2% w / w manganese.
[0057] Aspect 5. A composition according to any one of the preceding claims, comprising from about 1.4 to about 1.8%, preferably from about 1.5 to about 1.7%, or preferably from about 1.55 to about 1.65%, or preferably about 1.6% chromium w / w.
[0058] Aspect 6. A composition according to any one of the preceding claims, comprising about 1.3 to about 1.6%, preferably about 1.4 to about 1.5, or preferably about 1.45% w / w, or preferably about 1.5% w / w of molybdenum.
[0059] Aspect 7. A composition according to any one of the preceding claims, comprising from about 0.1 to about 0.3, preferably from about 0.15 to about 0.2, or preferably about 0.18% w / w niobium.
[0060] Aspect 8. A composition according to any one of the preceding claims, comprising from about 0.1 to about 0.3, preferably from about 0.15 to about 0.2, or preferably about 0.18% w / w vanadium.
[0061] Aspect 9. A composition according to any one of the preceding claims, comprising from about 1.5 to about 1.8%, preferably from about 1.5 to about 1.7%, or preferably from about 1.6 to about 1.7%, or preferably about 1.6% w / w silicon.
[0062] Aspect 10. A composition according to any one of the preceding claims, comprising from about 0.05 to about 0.14%, preferably from about 0.1 to about 0.14%, or preferably about 0.14% w / w carbon.
[0063] Aspect 11. The composition of any one of the preceding claims, further comprising sulfur.
[0064] Aspect 12. The composition of claim 11, comprising from about 0.001 to about 0.015%, preferably from about 0.005 to about 0.01%, or preferably from about 0.006 to 0.008%, or preferably about 0.007% w / w sulfur.
[0065] Aspect 13. A composition according to any one of the preceding claims, further comprising oxygen.
[0066] Aspect 14. The composition of claim 13, comprising from about 0.01 to about 0.1%, preferably from about 0.04 to about 0.08%, or preferably from about 0.05 to 0.07%, or preferably about 0.06% w / w sulfur.
[0067] Aspect 15. A composition according to any one of the preceding claims, further comprising nitrogen.
[0068] Aspect 16. The composition of claim 15, comprising from about 0.01 to about 0.02%, preferably from about 0.015 to about 0.015%, or preferably about 0.01% w / w nitrogen.
[0069] Aspect 17. The composition of any one of the preceding claims, wherein the composition is a metal powder.
[0070] 18. The composition of any one of the preceding claims, having a d of about 1 to about 10 μm. 10 Particle size: approx. 10 to approx. 20 μ 50 Particle size, or d of about 20 to about 30 μ 90 particle size, or a combination thereof.
[0071] Aspect 19. A method for preparing a metal powder, comprising the step of atomizing a composition according to any one of the preceding claims.
[0072] Aspect 20. The method of claim 18, wherein the atomizing step is gas or water atomization.
[0073] Aspect 21. A metal powder prepared according to the method of claim 18 or 19.
[0074] Aspect 22. The metal powder of claim 10, having a d of about 1 to about 10 μm. 10 Particle size: approx. 10 to approx. 20 μ 50 Particle size, or d of about 20 to about 30 μ 90 a metal powder having a particle size, a diameter, a diameter of a particle, or a combination thereof.
[0075] Aspect 23. A method of preparing a metal object, comprising subjecting the metal powder of claim 18 or 19 to metal binder jetting.
[0076] Aspect 24. The method of claim 20, comprising depositing two or more layers comprising the metal-fabrication composition of claim 1 on a substrate.
[0077] Aspect 25. The method of claim 21, wherein the layers are bonded using a liquid bonding agent.
[0078] Aspect 26. The method of any one of claims 20-22, further comprising the step of sintering the metal body.
[0079] Aspect 27. The method of claim 23, wherein the metal body is sintered in a temperature region in which the crystal structure of the alloy is body-centered cubic (BCC) ferrite.
[0080] Aspect 28. The method of claim 23 or 24, wherein the sintered metal body comprises a ratio of BCC to face-centered cubic austenite (FCC) of about 1:1.
[0081] Aspect 29. The method according to any one of claims 23 to 25, wherein the sintering temperature is about 700 to about 1500°C.
[0082] 30. The method of any one of claims 23 to 26, wherein the sintered metal body has a density of at least about 7 g / cm 3 That is, the method.
[0083] Aspect 31. The method of any one of claims 23-27, wherein the sintered metal body is annealed.
[0084] Aspect 32. The method of claim 28, wherein the intercritical annealing temperature is from about 600 to about 1000°C.
[0085] Aspect 33. A metal object prepared according to the method of any one of claims 23-32.
[0086] The following examples are provided to illustrate some of the concepts described within this disclosure. Each example is considered to provide a particular individual embodiment of the compositions, methods of preparation and uses, but no example should be considered to limit the more general embodiments described herein.
[0087] Working Example Example 1: Reagents and Procedures
[0088] The powders were gas atomized using nitrogen as the atomizing gas. Chemical analyses and powder properties are shown in Tables 1A and 1B. The particle size of each alloy is typical of that used for metal binder jetting. [Table 1] TIFF2024540861000002.tif46163
[0089] All test samples are printed with an HP Multi Jet Fusion printer at a layer thickness of 50 microns using water-based binders available in the art.
[0090] The specimens are sintered at DSH Technologies using an Elnik Systems MIM3045T furnace. These furnaces perform the thermal debonding and sintering process in one furnace. The equipment has a maximum temperature of 1600°C and allows partial pressure or vacuum control. The furnace has an all-metal process zone and allows atmosphere control of pure hydrogen, nitrogen, argon or vacuum. The specimens are sintered in the high temperature Elnik MIM at 1380°C for 30 minutes in an atmosphere of 95v / w nitrogen / 5v / w hydrogen.
[0091] For continuous heat treatment a high temperature Abbott type continuous belt furnace is used in an atmosphere of 95 v / w / nitrogen / 5 v / w hydrogen at the indicated temperature for 30 minutes.
[0092] Prior to mechanical testing, green and sintered density, dimensional change (DC), and apparent hardness were measured on tensile and transverse fracture (TR) specimens. Five tensile and five TR specimens were evaluated for each composition. The density of green and sintered steels was determined according to MPIF standard 42. Tensile tests were performed according to MPIF standard 10 and apparent hardness measurements according to MPIF standard 43 on tensile and TR specimens.
[0093] Porosity measurements are made on metallographically prepared cross sections removed from whole test parts. A Clemex automated image analysis system is used to measure and map porosity on the as-prepared surfaces, isolating dark void spaces from highly light reflective metallic areas, and estimating pore content in both the sample volume and localized areas.
[0094] Specimens for microstructural characterization are prepared using standard metallographic procedures, followed by optical microscopy in polished and etched (2v / o nital / 4w / o picral) condition.
[0095] Furthermore, colors are used in a two-step process of etching / staining to reveal the microstructure and to separate the transformation products. First, a light pre-etch defines the microstructure by immersing the sample in Vilella's reagent (5 ml HCl + 1 g picric acid + 100 ml ethyl alcohol), rinsing with warm water and drying with filtered compressed air. In a second step, the pre-etched sample is immersed in a freshly prepared solution of 10 g sodium metabisulfite (Na2S2O5) in 100 ml deionized or distilled water, rinsed with warm water and alcohol and dried with filtered compressed air.
[0096] Example 2: Alloy Design
[0097] For metal binder jetting, the as-built density obtained from the printer itself is usually not much higher than the apparent density of the powder (~60%). Currently, many AM machine manufacturers design roller systems to spread the powder and apply some force to the powder bed to densify the printed part, but the way the powder is packed into the print bed determines the final part density after printing. Figure 1 highlights that due to the lower initial density of parts printed from metal binder jet, a higher energy input is required to achieve a density typical of traditional powder metallurgy or MIM processes. Figure 1 shows that 316L specimens produced by metal binder jetting have as-built densities of 3.8-4.6 g / cm. 3 As an example, the typical density of MIM processed 316L before sintering is about 5.5 g / cm 3 In conventional powder metallurgy, the typical 3 (when compressed at 690 MPa). Thus, longer sintering times and higher sintering temperatures are required to achieve the same final density with metal binder jetting. Even when using a very fine powder size (8-12 microns) with a high as-built density, the material sintered at 1260 °C in 100 vol% hydrogen has a density of 7.0 g / cm. 3Only densities close to this can be achieved.
[0098] In this example, the metal powders of the present disclosure are shown to improve the sinterability of metal binder jetting parts; they sinter in a temperature range where the crystal structure of the alloy is body-centered cubic (BCC) ferrite rather than face-centered cubic austenite (FCC). Thus, the metal powders are balanced in composition to provide a nearly 50 / 50 mixture of austenite and ferrite at the sintering temperature (1380°C).
[0099] Metal powders are prepared using the amounts of carbon, silicon, manganese, molybdenum, nickel, and chromium shown in Table 2. [Table 2]
[0100] At temperatures above 1120°C, commonly used for sintering, the metal powders of the present disclosure form a high percentage of ferrite. Figure 2 compares the phase diagrams of the metal powders of the present disclosure with the conventional DP600 wrought alloy. The DP600 wrought alloy is a dual-phase wrought alloy consisting of approximately 20-25 vol% martensite in a ferritic matrix, typically produced by controlled rolling in combination with a secondary heat treatment. The DP600 wrought alloy is commonly used in automotive body construction.
[0101] In addition, the composition of conventional duplex stainless steels, consisting mainly of low carbon levels and up to 2% w / w manganese, is not suitable for sintering processes. In the disclosed metal powders, the temperature range in which the ferrite phase is present is very wide, corresponding to typical sintering temperatures (700-1400°C). Comparing the phases present in a standard duplex stainless steel (DP600) over the same temperature range, it can be seen that only austenite is present in the temperature window for sintering.
[0102] Another significant difference between the wrought DP600 compositions of the art and the metal powders of the present disclosure is the presence of niobium and vanadium.
[0103] Example 3: Density Considerations
[0104] Generally, metal binder jetting processes are not able to achieve full density compared to wrought grades unless special techniques such as liquid phase sintering or hot isostatic pressing (after initial sintering) are utilized, therefore higher temperatures and longer times are typically employed for sintering green parts.
[0105] The metal powder of the disclosure of Example 2 was tested to maximize density under these conditions. In summary, the metal powder of Example 2 was subjected to metal binder jetting to provide a green metal body, which was then sintered. The densities of the metal powder, green metal body, and sintered metal body were obtained. See Table 3, which shows the densities of metal bodies produced using DP600 wrought iron metal powder and the metal powder of the disclosure in terms of astomized (apparent density), as-built density (green density), and sintered density (final density). The change in density occurred during sintering. As both materials were subjected to the same sintering cycle, the metal powder of the disclosure exhibits superior sinterability over the DP600 product. At the sintering temperatures utilized, the DP600 product is in the austenitic form (100%), whereas the metal powder of the disclosure has a microstructure of about 50 vol% ferrite and about 50 vol% austenite. Furthermore, the density increase of the metal powder of the disclosure is greater than 1 g / cm 3 It is extremely dramatic, approaching [Table 3]
[0106] Example 4: Treatment of metal compositions
[0107] Intercritical annealing is a processing step in producing dual phase steels. The intercritical annealing temperature is selected to control the volume fraction of the ferrite and austenite phases (which are subsequently transformed during cooling). To ascertain the intercritical annealing temperature of the metal powders of the present disclosure to produce 20-30% of the transformation product (e.g., either bainite or martensite microstructures prepared by cooling), individual samples of the sintered metal body of Example 3 are heated to various temperatures within the austenite / ferrite region as shown in the FSLA phase diagram. See Figure 2. The samples are quenched and the level of ferrite phase in the microstructure is determined by microstructural analysis and compared to predictions using a thermodynamic software package (Thermocalc). The results of this experiment are shown in Figure 3.
[0108] In general, the agreement between the measured and predicted values was good. The results indicate that an intercritical annealing temperature of about 750-950°C is utilized to achieve a microstructure of about 20-30% bainite / martensite. Another factor in the intercritical annealing process is the cooling rate. Figure 4 is a continuous cooling transformation diagram (CCT diagram) of the metal powder of the present disclosure. See Tables 1A and 1B.
[0109] The cooling rate achieved utilizing a continuous belt furnace is shown on the CCT diagram in Figure 4 as the vertical line between hardness 498 and 522. The specimen was heated to 843°C and entered the two-phase region of the phase diagram (Figure 2) containing unstable austenite and stable ferrite. The maximum furnace cooling rate utilized was 1.3°C / s (shown as the vertical line between hardness 498 and 522). The CCT diagram shows that the unstable austenite transforms to bainite on cooling from 843°C. A cooling rate of 16-20°C / s is required to form martensite.
[0110] On cooling, the CCT curves show that the unstable austenite transforms to bainite at the cooling rate used. The resulting microstructure is shown in Figure 5. This structure shows that the original unstable austenite transforms to bainite and two different forms of ferrite. The transformation product (bainite) is surrounded by ferrite, which deforms due to the change in the crystal structure of the austenite on cooling and forms dislocations in the adjacent ferrite. Dislocations in ferrite generally result in an increase in the work hardening rate and increase the strength of the ferrite.
[0111] There is also a secondary ferrite located away from this transformation and adjacent to the unstressed dislocation ferrite. Table 4 shows the proportion of each phase and the corresponding microindentation hardness. The harder the ferrite has, the more dislocation structure it has. [Table 4]
[0112] FIG. 6 shows electron backscatter diffraction (EBSD) results of the microstructure of the annealed metal powder of the present disclosure. As known in the art, EBSD is a technique utilized to measure phase amounts and stresses in the microstructure of a metal object. These EBSD results show that the ferrite grains next to the transformation products (in this case bainite) contain a significant amount of dislocations. These dislocations contribute to the work hardening of the alloy, providing the metal object with high ultimate tensile strength with continuous yielding and high ductility.
[0113] The degree of precipitation strengthening in a metal object depends on the volume fraction, size, type, etc. of the precipitates. Figure 7 shows examples of precipitates formed in metal powders of the present disclosure after heat treatment. Examples shown by scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS) show the presence of both individual niobium-rich carbides along with a network of molybdenum-rich carbides. See spectral data in Tables 5 and 6. [Table 5] [Table 6]
[0114] When precipitates are present within the grains, they impede dislocation motion, increasing the strength and hardness of the alloy. After sintering, precipitates located at the grain boundaries pin the grain boundaries and limit grain growth during the intercritical annealing stage. This restriction of grain growth also increases the strength of the material.
[0115] The typical size of NbC, VN or TiC in forged steel is 2-100 nanometers. When the metal powder of the present disclosure is used and sintered at 1380°C in an atmosphere of 95% nitrogen and 5% hydrogen, NbC, VC and other alloy carbides are observed. The average size of the precipitates is 0.3-0.4 microns (300-400 nanometers), which contributes to the improvement of the strength of the metal object. See Figure 8. The precipitates are formed during sintering in the ferritic phase field. The precipitation strengthening was calculated for this coarse grain size using the following calculation and was found to be 40-50 MPa. See Figure 10. This is due to the large contribution of strength from precipitation hardening. TIFF2024540861000008.tif84145
[0116] Example 6: Properties
[0117] In this example, it is shown that the metal powder disclosed in Example 2, when sintered and heat treated with metal binder jetting, provides a metal object alloy that achieves mechanical property levels of conventional DP600 wrought alloy, i.e., an ultimate tensile strength of at least about 600 MPa.
[0118] To evaluate the mechanical properties and level of consistency of binder jet printing with sintering and heat treatment, separate print runs are processed for different times, with the same parameters for each step. The properties of these individual runs are shown in Table 7 along with typical forging specifications. The ultimate tensile strength and yield strength of the disclosed metal powder were similar to the forged DP600, but the elongation was slightly lower than the minimum. Based on the porosity data, the disclosed metal powder only achieved 97-98% of the theoretical density. [Table 7]
[0119] Example 7: Change in annealing temperature
[0120] As mentioned previously, one of the advantages of dual-phase materials is that they can be intercritical annealed at temperatures that change the levels of austenite and ferrite. Thus, heat treatments can be developed to produce a range of properties in the same alloy. See Figure 3.
[0121] The metal powders discussed herein can be utilized to meet various properties of the manufactured metal objects. For example, for metal binder jetting materials, the development of printing parameters and sintering profiles can take time and be influenced by the composition of the metal powder. The ability to cover a range of properties with one metal powder leads to faster material development and industrialization. Table 8 shows the property ranges achieved for FSLA materials with the same printing and sintering parameters but different intercritical annealing temperatures and cooling rates. [Table 8]
[0122] From Table 8, it can be seen that the FSLA alloys exhibit UTS strengths in the range of 700-800 MPa (a 15% increase) simply by changing the intercritical annealing temperature. As the strength increases, the ductility decreases.
[0123] While the promise of all additive manufacturing processes is high, metal binder jetting suffers from the fact that full density cannot be achieved without special techniques such as liquid phase sintering or hot isostatic pressing. Figure 8 shows a comparison of the disclosed metal powders with various heat treatments and carbon levels to a typical duplex stainless steel. As mentioned before, the disclosed metal powders still have residual porosity (about 2.5%), so the ductility is still lower than traditional duplex stainless steels (about 20% versus a minimum of 24%).
[0124] The contents of all references, patent applications, patents, and published patent applications cited throughout this application, as well as any figures, are hereby incorporated by reference.
[0125] Those skilled in the art will recognize, or be able to ascertain using no more than routine experimentation, many equivalents to the specific embodiments of the disclosure described herein which equivalents are intended to be encompassed by the following claims.
Claims
1. A composition comprising iron and about 0.01 to about 0.4% w / w manganese; about 1.3 to about 1.9% w / w of chromium; about 0.1% w / w or less of nickel; about 1.2 to about 1.7% w / w of molybdenum; about 0.01 to about 0.4% w / w of niobium; about 0.01 to about 0.4% w / w of vanadium, about 1.5 to about 2% w / w silicon, and about 0.01 to about 0.20% w / w of carbon; A composition comprising:
2. 10. The composition of claim 1, comprising 0% w / w nickel.
3. 2. The composition of claim 1 , (i) about 0.04 to about 0.1%, preferably about 0.05 to about 0.07%, or preferably about 0.05% w / w, or preferably about 0.1% w / w, of nickel; and / or (ii) about 0.1 to about 0.3%, preferably about 0.15 to about 0.25%, or preferably about 0.2% w / w manganese; and / or (iii) about 1.4 to about 1.8%, preferably about 1.5 to about 1.7%, or preferably about 1.55 to about 1.65%, or preferably about 1.6% chromium w / w; and / or (iv) about 1.3 to about 1.6%, preferably about 1.4 to about 1.5, or preferably about 1.45% w / w, or preferably about 1.5% w / w of molybdenum; and / or (v) about 0.1 to about 0.3, preferably about 0.15 to about 0.2, or preferably about 0.18% w / w of niobium; and / or (vi) about 0.1 to about 0.3, preferably about 0.15 to about 0.2, or preferably about 0.18% w / w vanadium; and / or (vii) about 1.5 to about 1.8%, preferably about 1.5 to about 1.7%, or preferably about 1.6 to about 1.7%, or preferably about 1.6% w / w silicon; and / or (viii) about 0.05 to about 0.14%, preferably about 0.1 to about 0.14%, or preferably about 0.14% w / w of carbon; A composition comprising:
4. The composition of claim 1, further comprising about 0.001 to about 0.015%, preferably about 0.005 to about 0.01%, or preferably about 0.006 to 0.008%, or preferably about 0.007% w / w of sulfur.
5. The composition of claim 1, further comprising about 0.01 to about 0.1%, preferably about 0.04 to about 0.08%, or preferably about 0.05 to 0.07%, or preferably about 0.06% w / w of oxygen.
6. The composition of claim 1, further comprising about 0.01 to about 0.02%, preferably about 0.015 to about 0.015%, or preferably about 0.01% w / w nitrogen.
7. The composition of claim 1, wherein the composition is a metal powder, optionally having a d 10 particle size of about 1 to about 10 microns, a d 50 particle size of about 10 to about 20 microns, or a d 90 particle size of about 20 to about 30 microns, or a combination thereof.
8. 8. A method for preparing a metal powder, said method comprising the step of atomizing a composition according to any one of claims 1 to 7, optionally said atomizing being gas or water atomization.
9. 10. A metal powder prepared according to the method of claim 8, optionally having a d10 particle size of about 1 to about 10μ, a d50 particle size of about 10 to about 20μ, or a d90 particle size of about 20 to about 30μ, or a combination thereof.
10. 10. A method of preparing a metal object, the method comprising subjecting the metal powder of claim 9 to metal binder jetting.
11. 11. The method of claim 10, comprising depositing two or more layers comprising the metal processing composition of claim 1 onto a substrate, optionally wherein the layers are bonded using a liquid bonding agent.
12. 11. The method of claim 10, further comprising sintering the metal body, optionally wherein the metal body is sintered in a temperature range where the crystal structure of the alloy is body-centered cubic (BCC) ferrite, optionally wherein the sintered metal body comprises a ratio of BCC to face-centered cubic austenite (FCC) of about 1:1, optionally wherein the sintering temperature is about 700 to about 1500°C, or optionally wherein the density of the sintered metal body is at least about 7 g / cm3.
13. The method of claim 12, wherein the sintered metal body is annealed, optionally at an intercritical annealing temperature of about 600 to about 1000°C.
14. A metal object prepared according to the method of claim 10.